2017
DOI: 10.3233/wor-172520
|View full text |Cite
|
Sign up to set email alerts
|

Split-shift work in relation to stress, health and psychosocial work factors among bus drivers

Abstract: BACKGROUND: Shift work has been associated with poor health, sleep and fatigue problems and low satisfaction with working hours. However, one type of shift working, namely split shifts, have received little attention. OBJECTIVE: This study examined stress, health and psychosocial aspects of split-shift schedules among bus drivers in urban transport. METHODS: A questionnaire was distributed to drivers working more than 70% of full time which 235 drivers in total answered. RESULTS: In general, drivers working sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 20 publications
1
27
0
4
Order By: Relevance
“…Furthermore, work-related stress of professional drivers has been associated with other adverse outcomes such as burnout , cardio-metabolic disease (Cohen, Kessler & Gordon, 1995; Brosschot, Pieper & Thayer, 2005; Spruill, 2010; Apostolopoulos et al, 2016) and poor mental and physical self-reported health (Stoynev & Minkova, 1997; Chung & Wong, 2011; Chung & Wu, 2013; Ihlström, Kecklund & Anund, 2017). Regarding mid and long-term outcomes, work stress may also explain worse results in, for instance, job adjustment (Schjott, 2002), job satisfaction (De Croon et al, 2002), and perceived well-being (O’Neill & Davis, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, work-related stress of professional drivers has been associated with other adverse outcomes such as burnout , cardio-metabolic disease (Cohen, Kessler & Gordon, 1995; Brosschot, Pieper & Thayer, 2005; Spruill, 2010; Apostolopoulos et al, 2016) and poor mental and physical self-reported health (Stoynev & Minkova, 1997; Chung & Wong, 2011; Chung & Wu, 2013; Ihlström, Kecklund & Anund, 2017). Regarding mid and long-term outcomes, work stress may also explain worse results in, for instance, job adjustment (Schjott, 2002), job satisfaction (De Croon et al, 2002), and perceived well-being (O’Neill & Davis, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the risk of injury in 1-5 hours between shifts may reflect more the effect of a long work day, instead of a quick return where employees can return to their home and rest. These unusual events of 1-5 hours between shifts could be due to on-call shifts or split shifts, where the work day is split into at least two work periods (41,42). The mechanisms linking quick returns to risk of injury are not yet determined.…”
Section: Discussionmentioning
confidence: 99%
“…Work-related depressed mood can be understood as a state of mind resulting from not being able to resolve the stress experienced in the work situation, thus resulting in too much negative stress (e.g., Niedhammer, Malard, & Chastang, 2015). Previous studies indicate that there is a causal relationship between stress and stress-related complaints, such that a high load of stress can lead to various forms of fatigue and depressed mood (e.g., Åkerstedt et al, 2014;Ihlström, Kecklund, & Anund, 2017;Shahid, Shen, & Shapiro, 2010). Stress-related conditions can therefore be described as different expressions and varying degrees of negative experiences linked to the work situation.…”
Section: Stress and Stress-related Complaints Among Teachersmentioning
confidence: 99%